Should I stay or should I go? Career choices for young workers in Latin America - Diana Martínez Heredia; Graciana Rucci; Fernando Saltiel; Sergio Urzúa (Inter-American Development Bank (IDB), 2018)
Labor market institutions shape the return to workers' skills. They define the incentives of firms and workers to invest in general and specific skills, affecting the returns to experience and tenure. This paper presents an empirical assessment of this hypothesis. We take advantage of rich administrative data from Brazil and Chile, two countries with different regulatory frameworks. We focus on young workers as they face to a greater extent the trade-off between accumulating general or specific skills. The analysis is motivated by a simple conceptual framework, from which we derive empirical predictions. It takes into account the potential endogeneity of occupational choices, while allowing for heterogenous returns to tenure and experience. We find positive average returns to both dimensions in both countries, with larger returns to tenure in Brazil and larger returns to experience in Chile. This is consistent with the original conjecture as the more rigid labor market legislation in Brazil encourages firms to carry out additional investments in young workers's specific skills. Chile's institutions, on the contrary, promote the acquisition of general skills. We further examine how these returns differ by educational attainment, an important policy consideration in the region, and find that more educated workers in both countries face larger returns to experience and tenure relative to their less educated counterparts.
Keywords: J01; J24; J31; J60; 330; Labor markets; youth employment; returns to skills; occupational mobility; heterogeneity